O tempo performático de samuel beckett: o teatro da condição humana no processo de montagem de esperando godot do máskara (2005) - Reis, Adriel Diniz dos (2015)
The purpose of this communication is to present and analyze the representation of theatrical performance Waiting for Godot by Samuel Beckett, promoted by Máskara – Núcleo Transdisciplinar de Pesquisa em Teatro, Dança e Performance, from Escola de Música e Artes Cênicas (EMAC), Universidade Federal de Goiás (UFG) in 2005. This examination is based on the concept of performative time drawn from the analysis of prospects that blend the study of performances of Richard Schechner and Victor Turner, with time trials established in studies and reflections of Henri Bergson, Marcel Proust, Reinhart Kosellec and Paul Ricoeur, in conjunction with the practical discussions emerged in the production of Beckett presentation, as well as the dialectic of the human condition and time established by Beckett in that piece. Performers, time and human nature dialogues, construction, perception and representation of theatrical production are made. All these actions will be closely articulated in the development of this research in order to understand and explain this process, and as such proposals reflections approximate the studies inherent Cultural Performances, the work of the Máskara and reflections and concepts proposed by playwright in the theatrical text Waiting for Godot.